(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Muscular dystrophy-dystroglycanopathy refers to a group of autosomal recessive neurodegenerative disorders resulting from homozygous or compound heterozygous mutations in the gene encoding POMGNT1 O-mannose β-1,2-N-acetylglucosaminyltransferase. The clinical presentation of this form of muscular dystrophy typically includes early-onset muscle weakness, gait ataxia, microcephaly, and growth delay. A case study was conducted on an 8-year-old Iranian male displaying symptoms such as microcephaly, seizures, hydrocephalus, cerebellar abnormalities, glaucoma, growth delay, and lissencephaly. The parents of the affected child were found to be heterozygous for the POMGNT1 gene. Within the scope of this investigation, a novel duplication (dup1834c) was identified in exon 21 of the POMGNT1 gene. The presence of dup1834c in the POMGNT1 gene was verified through Sanger sequencing in the affected individual and other family members affected by the disease.